Regulation of root hair cell differentiation by R3 MYB transcription factors in tomato and Arabidopsis - Tominaga-Wada, Rumi; Wada, Takuji (Frontiers in Plant Science, 2014)
CAPRICE (CPC) encodes a small protein with an R3 MYB motif and regulates root hair and trichome cell differentiation in Arabidopsis thaliana. Six additional CPC-like MYB proteins including TRIPTYCHON (TRY), ENHANCER OF TRY AND CPC1 (ETC1), ENHANCER OF TRY AND CPC2 (ETC2), ENHANCER OF TRY AND CPC3/ CPC-LIKE MYB3 (ETC3/CPL3), TRICHOMELESS1 (TCL1) and TRICHOMELESS2/CPC-LIKE MYB4 (TCL2/CPL4) also have the ability to regulate root hair and/or trichome cell differentiation in Arabidopsis. In this review, we describe our latest findings on how CPC-like MYB transcription factors regulate root hair cell differentiation. Recently, we identified the tomato SlTRY gene as an ortholog of the Arabidopsis TRY gene. Transgenic Arabidopsis plants harboring SlTRY produced more root hairs, a phenotype similar to that of 35S::CPC transgenic plants. CPC is also known to be involved in anthocyanin biosynthesis. Anthocyanin accumulation was repressed in the SlTRY transgenic plants, suggesting that SlTRY can also influence anthocyanin biosynthesis. We concluded that tomato and Arabidopsis partially use similar transcription factors for root hair cell differentiation, and that a CPC-like R3 MYB may be a key common regulator of plant root-hair development.